AI-based mind mapping in project-based learning: Impact on students’ collaboration skills - Miswandi Tendrita; Ully Hidayati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Collaboration skills are essential skills that students must have in the era of higher education, where they must work together to complete complex tasks. This study intends to examine the effectiveness of project-based learning (PjBL) supported by artificial intelligence-driven mind mapping in enhancing the collaboration skills of pre-service biology teachers. The research was conducted in the Biology Education Department at the Sembilanbelas November Kolaka University, involving a student in their sixth semester. A controlled pretest-posttest experimental design was employed, and a collaboration observation sheet was developed based on collaboration skill indicators as the research instrument. Descriptive analysis demonstrated an increase in students’ collaboration skills, with the average score improving from 57.99 before treatment to 69.33 after treatment. Furthermore, inferential analysis using a paired sample t-test yielded a significance value of 0.000 < 0.05, indicating a statistically significant difference. These results suggest that implementing PjBL with AI-powered mind mapping contributes to collaboration skills among biology education students.